Evaluating Workplace Mandates with Flows versus Stocks: An Application to California Paid Family Leave - Mark Curtis; Barry Hirsch; Mary C. Schroeder (Institute for the Study of Labor (IZA), 2014)
Employer mandates and other labor demand/supply shocks typically have small effects on wages and employment. These effects should be more discernible using data on employment transitions and wages among new hires rather than incumbents. The Quarterly Workforce Indicators (QWI) dataset provides county by quarter by demographic group data on the number and earnings of new hires, separations, and recalls (i.e., extended leaves). We use the QWI to examine the labor market effects of California's paid family leave (CPFL) policy. Implemented in July 2004, it was the first such policy mandated in the U.S. The analysis compares outcomes for young women in California to those for other workers in California and to workers throughout the U.S. Relative earnings for young female new hires were largely unaffected by CPFL. We find strong evidence that separations (of at least three months) and hiring of young women increased substantively. Many young women who separated later returned to the same firm. CPFL appears to have led not only to increased time with children, but also to a decline in job lock, enhanced mobility, and increased worker flows following universal paid family leave.
Keywords: J32; J38; 330; policy evaluation; paid family leave; new hires; wages; employment; turnover